2018
DOI: 10.1371/journal.pone.0197523
|View full text |Cite
|
Sign up to set email alerts
|

The effect of adjuvant chemotherapy on survival in Korean patients with node negative T1c, triple negative breast cancer

Abstract: BackgroundThe present study investigated the prognostic role of adjuvant systemic chemotherapy in patients with node negative, T1c triple negative breast cancer (TNBC) from a nationwide cohort. In addition, the prognostic effect between 3 different chemotherapy regimens were compared in node-negative T1c TNBC patients by subgroup analysis.MethodsFrom the Korean breast cancer registry database, 1,151 T1c node negative TNBC patients were included in this study. Patients were categorized into four treatment group… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 19 publications
1
6
0
Order By: Relevance
“…However, we found no significant difference in survival between patients treated with this intensive regimen and those receiving other less intensive regimens including CMF, anthracycline-based and taxane-based regimens. This result is in keeping with several other retrospective reports 17,23,31 and the current study results provide a basis for the design of future prospective trials. Therefore, it is reasonable to consider less intensive chemotherapy for patients with T1cN0M0 TNBC, which is consistent with current guidelines.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…However, we found no significant difference in survival between patients treated with this intensive regimen and those receiving other less intensive regimens including CMF, anthracycline-based and taxane-based regimens. This result is in keeping with several other retrospective reports 17,23,31 and the current study results provide a basis for the design of future prospective trials. Therefore, it is reasonable to consider less intensive chemotherapy for patients with T1cN0M0 TNBC, which is consistent with current guidelines.…”
Section: Discussionsupporting
confidence: 93%
“…Some studies have demonstrated poor outcomes for patients with T1N0M0 TNBC who are treated without chemotherapy, and adjuvant chemotherapy significantly improved survival accordingly. [22][23][24] By contrast, other studies could not prove the benefit of adjuvant chemotherapy. [14][15][16]19,20 One of the important reasons for this disparity might be the difference in the definition of "small" tumors used in these studies.…”
Section: Discussionmentioning
confidence: 93%
“…According to clinical trials, the TNBC subtype is more sensitive to chemotherapy and has higher pathologic complete response (pCR) rates than non-TNBC subtypes [6]. A real-world study revealed that chemotherapy significantly increased the overall survival rate (adjusted HR = 0.58, 95% CI = 0.46-0.73) and breast cancer-specific survival rate (adjusted HR = 0.65, 95% CI = 0.48-0.89) of TNBC patients during the 8.2-year median follow-up [7,8]. However, a sustained response can only be observed in a small proportion of TNBC patients and chemoresistance eventually develops in most patients.…”
Section: Introductionmentioning
confidence: 99%
“…However, the benefits seen in survival may be attributed to the selection of healthier individuals. Radiation was more likely to be omitted in elderly patients with a higher number of comorbidities [ 13 , 14 , 18 , 19 , 20 ]. In our study, we examined BCSS as opposed to OS due to the competing risk of mortality from associated comorbidities and age.…”
Section: Discussionmentioning
confidence: 99%